Race-track modelling and variability in RTM for advanced composites structures - Koutsonas, Spiridon (2015)
The Resin Transfer Moulding (RTM) process is one of the most common manufacturing routes for composites. The challenge in the present work is to be able to predict the flow behaviour in order to manufacture advanced composites truss structures. To that end, there is a lack of an advanced simulation tool capable to predict void formations for the manufacture of three dimensional, multi-layer woven textile composites like the Advanced Composites Truss Structure (ACTS) generic node TSB-funded project that is presented in this thesis. Industrial experience has shown that during mould filling, due to race-tracking and stochastic variability in the material properties, the filling patterns and arising cycle times are rarely the same between a given set of apparently identical mouldings.